Modifikasi Teorema Konvolusi Transformasi Kanonikal Linier Quaternion Sisi Kiri - Resnawati; Oktaviana, W; Musdalifah, S (Program Studi Matematika, Universitas Tadulako, 2019)
ABSTRACTQuaternion Linear Canonical Transform (QLCT) is a generalization of the Linear Canonical Transform (LCT) onquaternion algebra which plays an important role in optics and signal processing. QLCT can be seen asgeneralization of Quaternion Fourier Transform (QFT). Based on the fact, this paper propose the formulat ofmodification convolution theorem based on left-sided QLCT by considering the fundamental relationship betweenleft-sided QLCT and QFT. The results showed the modification convolution theorem for left-sided QLCT based onrelationship between left-sided QLCT and QFT as a sum of multiplication of left-sided QFT can be derived.Keywords : Convolution Theorem, Quaternion Fourier Transform, Quaternion Linear Canonical Transform